(untitled) (Nordic Journal of African Studies, 2011)
It has been argued that being raised in a transnational social field, second-generation migrants are not only socialized into the local practices of their country of settlement but also into those rules and institutions that characterize their country of origin or the birthplace of their parents. Going beyond this, I would argue that there is a need to explore to what extent this socialization process creates opportunities, and what prospects there are for individuals to make use of them. What specific social, cultural and material resources or capabilities are accumulated in a transnational life course? Given that human development and mobility are intrinsically relational in nature, an agency-oriented ethnographic approach to human development and its articulations at individual rather than community level seems crucial.